Teaching Psychology and Climate Change: One Way to Meet the Call for Action. (July 2018) - Maier, Karl J.; Whitehead, George I.; Walter, Mark I.
The American Psychological Association (APA) has called for psychologists to become more involved in addressing climate change. One way to address this pressing issue is through curriculum. To this end, we describe an undergraduate course that we created and teach exclusively focused on the interface of psychology and global climate change. The course is a seminar structured around three broad themes: science and impacts, adaptation, and solutions. To support others developing curriculum in this area, we explain these themes and share the course organization and structure, along with our experiences in teaching it. We provide relevant examples of activities and resources in the context of the goals and outcomes of APA's "Guidelines for the Undergraduate Psychology Major." We discuss considerations of competence and interdisciplinarity in teaching on this issue. Finally, given the magnitude and significance of climate change, we consider experiential aspects of students in the course related to stress.